2023
DOI: 10.1002/pits.22877
|View full text |Cite
|
Sign up to set email alerts
|

Influence of guidance knowledge and counseling services and attitudes toward guidance on the performance of guidance teachers in high schools

Abstract: Guidance and counseling teachers play an important role in students' career planning and dealing with students' problems.The primary objective of this study is to examine the influence of knowledge of guidance and counseling services as well as attitudes toward guidance on the performance of high school guidance teachers by measures of partial and multiple correlation. This study was conducted with a quantitative approach using the explanatory survey method. By employing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Many studies link work motivation with employee performance, which is still inconsistent. Several studies showed that the motivation to work owned by employees in an organization turned out to have a significant effect on employee performance (Vidianingtyas and Putri, 2014;Ahmad et al, 2014;Achmad, 2016;Rina and Perdana, 2017;Rahim et al, 2017;Gala et al, 2017;Basalamah, 2017;Hidayah and Tobing, 2018;Soebyakto et al, 2019;Parashakti et al, 2020;Sari et al, 2020;Hardianto et al, 2020;Marlinda et al, 2021;Kurniawati and Tobing, 2019;Riyadi, 2020;Koni, 2018;Ariono, 2017;Komaling et al, 2016;Hanafi and Abadi, 2018;Firdaus et al, 2017;Sumowo, 2017;Hermawan, 2015;Basyah et al, 2022;Solikah et al, 2016;Anggrainy et al, 2017;Afriadie et al, 2017;Kahpi et al, 2017;Utomo et al, 2019;Sumowo, 2017;Sya'roni et al, 2018;Hermawan, 2015;Indarti, 2018;Istanti et al, 2020;Sujana, 2012;Prakoso et al, 2014). In addition, there are also research results which showed that the work motivation of a person does not affect the performance of employees in an organization (Rantesalu et al, 2017;Julianry et al, 2017;Adha et al, 2019;…”
mentioning
confidence: 99%
“…Many studies link work motivation with employee performance, which is still inconsistent. Several studies showed that the motivation to work owned by employees in an organization turned out to have a significant effect on employee performance (Vidianingtyas and Putri, 2014;Ahmad et al, 2014;Achmad, 2016;Rina and Perdana, 2017;Rahim et al, 2017;Gala et al, 2017;Basalamah, 2017;Hidayah and Tobing, 2018;Soebyakto et al, 2019;Parashakti et al, 2020;Sari et al, 2020;Hardianto et al, 2020;Marlinda et al, 2021;Kurniawati and Tobing, 2019;Riyadi, 2020;Koni, 2018;Ariono, 2017;Komaling et al, 2016;Hanafi and Abadi, 2018;Firdaus et al, 2017;Sumowo, 2017;Hermawan, 2015;Basyah et al, 2022;Solikah et al, 2016;Anggrainy et al, 2017;Afriadie et al, 2017;Kahpi et al, 2017;Utomo et al, 2019;Sumowo, 2017;Sya'roni et al, 2018;Hermawan, 2015;Indarti, 2018;Istanti et al, 2020;Sujana, 2012;Prakoso et al, 2014). In addition, there are also research results which showed that the work motivation of a person does not affect the performance of employees in an organization (Rantesalu et al, 2017;Julianry et al, 2017;Adha et al, 2019;…”
mentioning
confidence: 99%